Minangkabau Cultural Values as Social Capital for Strengthening Students' Entrepreneurial Intentions: Evidence from Indonesia - Marleni Marleni; Disman Disman; Hari Mulyadi; Neiny Ratmaningsih; Enok Maryani; Rika Verawati; Verawati Verawati (Journal of Innovation in Educational and Cultural Research, 2026)
Cultural values are recognized as drivers of entrepreneurial intentions, particularly in communities with strong economic and social traditions, such as the Minangkabau ethnic group, which possesses a high work ethic and entrepreneurial tradition. These values have the potential to serve as social capital to enhance students' entrepreneurial intentions amid the high unemployment of university graduates. This study aims to examine the role of Minangkabau cultural values as social capital in entrepreneurship programs, as well as how these values are internalized by students to shape entrepreneurial intentions. A cross-sectional survey was conducted with 442 students in West Sumatra using validated instruments, and the analysis was performed with Structural Equation Modeling (SEM) using Smart-PLS to test direct, mediating, and moderating effects. The findings indicate that Minangkabau cultural values strongly predict social capital and directly enhance entrepreneurial intentions. Social capital significantly mediates this relationship, while the internalization of cultural values shows a small positive effect but a negative moderating effect, indicating a substitution mechanism between practical experience and overall cultural orientation. This study highlights the importance of integrating cultural value strategies and social capital in entrepreneurship education and contributes to the understanding of culture-based entrepreneurship and social capital theory.